2017
DOI: 10.5414/cn109126
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphism in the FKBP5 gene with response to steroids in pediatric patients with primary nephrotic syndrome

Abstract: The current data indicate that assessment of FKBP5 mutations could provide a basis for the identification of primary NS patients more likely to be efficiently treated with steroids.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interestingly, this could also hold true for nephrotic syndrome patients as well. Recently, one study was published on the potential role of FKBP5 polymorphism (rs4713916) in a small group of pediatric nephrotic syndrome patients showing a higher frequency in patients with a steroid-dependent nephrotic syndrome [ 73 ].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Interestingly, this could also hold true for nephrotic syndrome patients as well. Recently, one study was published on the potential role of FKBP5 polymorphism (rs4713916) in a small group of pediatric nephrotic syndrome patients showing a higher frequency in patients with a steroid-dependent nephrotic syndrome [ 73 ].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Interestingly, Russo et al ( 58 ) found that FKBP5 rs4713916 may a useful predictor of clinical outcomes for pharmacogenomic intervention for chronic obstructive pulmonary disease ( 58 ). According to Du et al ( 59 ) there was a significant difference in the frequency of the minor allele genotype of FKBP5 rs4713916 between the group of pediatric patients with primary nephrotic syndrome and the controls ( p = 0.024) and between the group with steroid-dependent nephrotic syndrome and controls ( p = 0.041) ( p = 0.041) ( 59 ). In contrast, few investigations regarding FKBP5 rs6926133 in physiological disease have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Musante et al [437], Han et al [438], Zhang et al [439], Sato et al [440], Yang et al [441], El-Aouni et al [442], Perisic et al [443], Chung et al [444], Wilkening et al [445], Kahvecioglu et al [446], Hu et al [447] and Worthmann et al [448] revealed that ALB (albumin), KLF15, ATF3, LPL (lipoprotein lipase), CUBN (cubilin), ILK (integrin linked kinase), PLEKHH2, TNF (tumor necrosis factor), CCR2, SPON2, LRRC55 and IGFBP1 might be the potential targets for FSGS diagnosis and treatment. Alves et al [449], Ma et al [450], Esposito et al [451], Ai et al [452], Lu et al [453], Bui et al [454], Bao et al [455], Zuo et al [456], Su et al [457], Wang et al [458], Šalamon et al [459], Harskamp et al [460], Ćwiklińska et al [461], Hishida et al [462], Gunay-Aygun et al [463], Simpson et al [464], Svenningsen et al [465], Wang et al [466], Rao et al [467], Chen et al [468], Bedin et al [469], Cao et al [470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474], Liu and Zhuang [475], Feng et al [476], Yu et al [477], Reed et al [478], Milillo et al [479], Chen et al [74], Chen et al [480], Vieira et al [76], Charlton et al [481], Shi et al [482], Zhou et al [483], Nazari et al [241], Greene et al [484], Lazar et al [485], Jobst-Schwan et al [486], Du et al [487], Liu et al [85], Liu et al [488], Liu et al [489], Lee et al [490], Wen et al [491], Sakai et al [492], Zhang et al [493], Wang et al [494], CD5L Castelblanco et al [251], Chen et al [495], Swanson et al [496], Ksiazek, [497], Li et al [498], Zhang et a...…”
Section: Discussionmentioning
confidence: 99%